Global Financial Reform Since 2008: Achievements and Shortcomings - Šoškić, Dejan (Panoeconomicus, 2015)
The global financial crisis that started in the U.S. had an immediate spillover to the rest of the world financial markets. Next, a decrease in real economic output throughout the developed world occurred simultaneously with high bailout costs for the salvaging of banks and other financial institutions. This vicious combination was at the core of the bank-sovereign interdepen- dence and the sovereign debt crisis of the eurozone. As early as 2008, the G20 announced a thorough global reform agenda with an aim to tackle the root causes of the crises and to transform the system of global financial regulation. Some important reform steps have been made; still, more than six years on, the job is not finished. Where are we in terms of global financial reform, and are we close to creating a more secure global financial system significantly less prone to crisis and bailouts with taxpayers’ money? Key words: Financial crisis, G20, Financial stability, Financial reform. JEL: E44, F33, F42, G28.